Commitment to Change among Government Accountants in Malaysia - Isa, Che Ruhana; Saleh, Zakiah; Jusoh, Ruzita (Asian Journal of Business and Accounting, 2017)
Reforms in the Malaysian public sector have significantly changed its structure and activities, which have in turn led to more complex administration and financial consequences. Much of these reforms such as changes in budgeting and reporting systems affect financial management, and require the commitment of government accountants. To ensure these reforms achieve the targets set, effective flows of Change messages, and employee commitment, are paramount. Five types of Change messages that are argued to affect commitments to Change are: (1) the organisational need for Change (discrepancy), (2) resulting appropriate corrective actions which are then necessary to eliminate discrepancy (appropriateness), (3) perceived capability to implement the Change initiative (efficacy), (4) the support of organisational leaders (principal support), and (5) the benefits of the Change to the individual (personal valence). In view of the importance of commitment to Change in achieving the aims of these reforms, it is pertinent to examine the roles of Change messages and flows of communication in enhancing commitment to Change, among government accountants. A survey was conducted on a sample of 163 government accountants in Malaysia. Consistent with expectations, the results reveal positive and significant associations among the Change messages and Communication flows with commitment to Change, suggesting that communication about the Change initiatives to employees is crucial in ensuring commitment to the Change programs and which will ultimately determine their success. Keywords: Change message, Communication flows, Commitment to change, Public sector accountant